Prenatal care perception of Saudi females of childbearing age: an epidemiological study - Alqifari, Saleh F.; Alharbi, Fahad A.; Algeffari, Abdulrahman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The purpose of this study is to assess perception of Saudi women of childbearing age regarding prenatal care. Methods: Participants were invited to participate in a voluntary online survey. The brief survey consisted of 15 basic multiple choice questions administered in Arabic, and delivered as a secure link through private social media messaging services. The survey permitted only 1 attempt per user. In order to reach and capture non-respondents, 2 follow-up reminders 10 days apart were sent through the same channels of communication. The survey data was collected and analyzed using the survey software platform, Qualtrics by Qualtrics © LLC 2017. Results: Approximately 9% of participants reported previous pregnancy without use of prenatal care. Nearly 12% of respondents thought that prenatal care is only indicated for malnourished pregnant females, and 7% reported not knowing who prenatal care is specifically indicated for. Nearly 21% reported prenatal care should start after confirmation of pregnancy, 14% thought proper start is anytime within the first 3 months, 8% reported proper start should be after confirmation of healthy pregnancy and 8% reported not sure when to initiate prenatal care. Approximately 12% thought taking prenatal vitamins should be once weekly or some days of the week, while 5% do not advice women to take prenatal vitamins during pregnancy at all. Conclusions: The majority of Saudi women are well educated on prenatal care. However, women in early and late twenties are less aware of proper usage of prenatal care.